NuSTAR results and future plans for magnetar and rotation‐powered pulsar observations. (March 2014) - An, H.; Kaspi, V.M.; Archibald, R.; Bachetti, M.; Bhalerao, V.; Bellm, E. C.; Beloborodov, A. M.; Boggs, S. E.; Chakrabarty, D.; Christensen, F. E.; Craig, W. W.; Dufour, F.; et al.
Abstract The Nuclear Spectroscopic Telescope Array (NuSTAR) is the first focusing hard X‐ray mission in orbit and operates in the 3–79 keV range. NuSTAR's sensitivity is roughly two orders of magnitude better than previous missions in this energy band thanks to its superb angular resolution. Since its launch in 2012 June, NuSTAR has performed excellently and observed many interesting sources including four magnetars, two rotation‐powered pulsars and the cataclysmic variable AE Aquarii. NuSTAR also discovered 3.76‐s pulsations from the transient source SGR J1745–29 recently found by Swift very close to the Galactic center, clearly identifying the source as a transient magnetar. For magnetar 1E 1841–045, we show that the spectrum is well fit by an absorbed blackbody plus broken power‐law model with a hard power‐law photon index of ∼ 1.3. This is consistent with previous results by INTEGRAL and RXTE. We also find an interesting double‐peaked pulse profile in the 25–35 keV band. For AE Aquarii, we show that the spectrum can be described by a multi‐temperature thermal model or a thermal plus non‐thermal model; a multi‐temperature thermal model without a non‐thermal component cannot be ruled out. Furthermore, we do not see a spiky pulse profile in the hard X‐ray band, as previously reported based on Suzaku observations. For other magnetars and rotation‐powered pulsars observed with NuSTAR, data analysis results will be soon available. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)